Candesartan effectiveness in essential arterial hypertension and renal arterial hypertension - N. M. Chikhladze; O. A. Sivakova; E. V. Blinova; T. A. Sakhnova; I. P. Kolos; G. N. Litonova; I. E. Chazova (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study candesartan effectiveness and tolerability in essential arterial hypertension (ГАН) and AH associated with chronic renal disease.Material and methods. This 12-week open, controlled study included 14 patients (mean age 43,4±16 years) with diagnosed ГАН (n=9) or secondary AH of renal etiology (n=5). At baseline and after 12 weeks of candesartan therapy, office blood pressure (BP) measurement, 24-hour BP monitoring (BPM), vectorcardiography and decar-tography measurements of plasma renin activity, aldosterone, potassium levels and microalbuminuria (MAU) were performed.Results. Target BP level <140/90 mm Hg was achieved in 6 out of 14 patients (42,8 %). Additional hydrochlorothiazide (HCT) therapy increased antihypertensive effect of candesartan. On average, MAU reduced from 63,5±16,8 to 31,7±24,4 mg/d (p<0,0001).Conclusion. Candesartan therapy, especially combined with HCT, was effective in patients with mild to moderate AH, providing organo-protection. It could be recommended not only in ГАН, but also in symptomatic AH associated with chronic renal disease.